Effect of mocaf-soybean flour ratio on nutritional composition and antioxidant activity of gluten free snack bars - Sutrisno Adi Prayitno; Dwi Retnaningtyas Utami; Reza Astika Wahyu Pramesti; Hesti Rahmawati (AcTion: Aceh Nutrition Journal, 2026)
Innovations in gluten-free snacks based on local ingredients, such as fermented mokaf and soy flour, have the potential to produce healthier functional foods and support dietary diversity. This study aimed to assess the effects of varying mokaf-soy flour ratios on the nutritional profile and antioxidant capacity of snacks. Methods: This study used a completely randomized design with six formulations (100:0 to 0:100) and three replicates. The study was conducted at the Food Chemistry and Analysis Laboratory and Agricultural Product Processing Technology Laboratory, Muhammadiyah University Gresik, from November 2025 to January 2026. The parameters analyzed included moisture, ash, protein, fat, carbohydrate, calcium, iron, total phenolic contents, and antioxidant activity using the DPPH method. Data were analyzed using ANOVA and Tukey's post hoc test. The results showed that an increase in the proportion of soybean flour reduced the moisture (4.45% to 2.92%) and carbohydrate (78.45% to 69.80%) (p<0.05) contents. The protein content increased from 5.36% to 23.59%, calcium from 227 to 350 mg/100 g, and iron from 34.8 to 44.8 mg/100 g. The total phenolic content increased and the IC₅₀ value decreased, indicating stronger antioxidant activity. In conclusion, soy flour substitution improved the nutritional quality and antioxidant potential of the snacks. A mixed formulation is recommended to balance functional value and consumer acceptance, accompanied by further evaluation of its stability and sensory quality.